Permainan Bola Basket Modifikasi, Strategi Pembelajaran Inovatif Untuk Meningkatkan Ketrampilan Variasi Dan Kombinasi Gerak Dasar Dalam Permainan Bola Besar Sederhana di MIN 2 Pemalang (BEST PRACTICE) - Ibrohim, Ahmad (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
A teacher who delivers teaching with good and innovative strategies, will create an interesting learning atmosphere and also improve the skills of students.This studyaims to provide information on the application of modified basketball games as an innovative learning strategy that can improve basic movement variations and combination skills in simple big ball games at MIN 2 Pemalang. This research was conducted in August 2022 with the best practice method in the learning process that was carried out in August 2022 at Madrasah Ibtidaiyah Negeri 2 Pemalang. Best Practice is the